2023
DOI: 10.3390/antib12020037
|View full text |Cite
|
Sign up to set email alerts
|

Serological Response to SARS-CoV-2 Vaccine in Hemodialyzed Patients and the Association with Later COVID-19 Positivity

Vedran Premuzic,
Ranko Stevanovic,
Tatjana Vilibic-Cavlek
et al.

Abstract: Background: The effectiveness of the COVID-19 vaccine may differ in hemodialysis patients. The aim of this prospective multicenter study was to determine the degree of serological response to the SARS-CoV-2 vaccine in the population of dialysis patients and its association with later SARS-CoV-2 infections. Methods: A blood sample was taken for the determination of COVID-19 serological status (IgG antibodies) in 706 dialysis patients 16 weeks after vaccination with the second dose (Pfizer-BioNTech). Results: On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
3
3
0
Order By: Relevance
“…The mean of anti-SARS-CoV-2 IgG class antibodies titers three to four weeks after the second vaccine dose was more than twice lower in hemodialysis patients as compared to controls in our study. Similarly, in other studies, patients undergoing dialysis exhibited lower antibody titers than the general population [20,21,[31][32][33]. The results of the study from Israel were similar to ours.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The mean of anti-SARS-CoV-2 IgG class antibodies titers three to four weeks after the second vaccine dose was more than twice lower in hemodialysis patients as compared to controls in our study. Similarly, in other studies, patients undergoing dialysis exhibited lower antibody titers than the general population [20,21,[31][32][33]. The results of the study from Israel were similar to ours.…”
Section: Discussionsupporting
confidence: 90%
“…[20] and Anand S. [37] also found similar correlations between immune response and serum albumin levels. Premuzic V. et al, as well as our study, did not find associations between hemoglobin, serum calcium, phosphates, creatinine levels and immune response [33].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Numerous studies have indicated that cohorts of people with chronic diseases and those receiving immunosuppressive medication have inadequate immune responses to COVID-19 [ 48 ]. The hemodialysis population does not show the same serological response to SARS-CoV-2 vaccination as immunocompetent people [ 49 ]. In addition, the serological response to SARS-CoV-2 vaccination is also diminished in the elderly.…”
Section: Discussionmentioning
confidence: 99%